2001
DOI: 10.1002/jnr.1195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyclic AMP on the expression of myelin basic protein species and myelin proteolipid protein in committed oligodendrocytes: Differential involvement of the transcription factor CREB

Abstract: Our previous results support the idea that CREB (cyclic AMP-response element binding protein) may be a mediator of neuroligand and growth factor signals that, coupled to different signal transduction pathways, play different roles at specific stages of oligodendrocyte development. In the early stages, when cells are immature precursors, CREB may play a role as a mediator of protein kinase C (PKC)/mitogen-activated protein kinase (MAPK) pathways regulating cell proliferation. In contrast, at a later stage, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…It was found that stimulation of the nuclear TPR pool caused an elevation in nuclear cAMP levels. Furthermore, this elevated cAMP was found to activate CREB, which is known to promote OLG survival (20,42) and stimulate MBP expression (1,43). The direct association of TPRs with MBP expression was confirmed in subsequent experiments, revealing nuclear TPR-mediated increases in MBP mRNA levels.…”
mentioning
confidence: 72%
“…It was found that stimulation of the nuclear TPR pool caused an elevation in nuclear cAMP levels. Furthermore, this elevated cAMP was found to activate CREB, which is known to promote OLG survival (20,42) and stimulate MBP expression (1,43). The direct association of TPRs with MBP expression was confirmed in subsequent experiments, revealing nuclear TPR-mediated increases in MBP mRNA levels.…”
mentioning
confidence: 72%
“…Treatments that induce a sustained elevation of cAMP levels in oligodendrocytes activate CREB and subsequently increase MBP protein levels by activating the MBP promoter (24,26,27,44). Conversely, inactivation of CREB has been reported in the presence of inhibitors of oligodendrocyte maturation, such as GSK3␤ (45) or CNS myelin (12).…”
Section: Discussionmentioning
confidence: 99%
“…One of the best characterized PKA-activated transcription factors is CREB, which is known to stimulate MBP expression in oligodendrocytes (24,26,27). To examine whether activation of CREB in rat differentiating oligodendrocytes is altered upon GPR17 stimulation, we measured CREB phosphorylation in the presence of MDL29,951.…”
Section: Effects Of Gpr17 Stimulation On Protein Kinase a Function Anmentioning
confidence: 99%
“…Several studies have shown that OLG differentiation is stimulated by cAMP (McMorris, 1983;Pleasure et al, 1986;McMorris, 1989, 1990) and elevated levels of the transcription factor CREB, which mediates cAMP-dependent stimulation of MBP expression and the outgrowth of OLGc processes (Sato-Bigbee et al, 1994Sato-Bigbee and De Vries, 1996;Afshari et al, 2001). Skorupa and McMorris (1995) reported that in OLGcs cultured during 1-8 days in vitro, increased cAMP levels upregulated MBP and PLP genes, whereas after 8 days in vitro, these genes were downregulated, suggesting that the effect of cAMP on OLGcs depends on the maturation of the cells.…”
Section: Introductionmentioning
confidence: 98%